Theoretical Modification of Cyanidin as Sensitizers in Dye Sensitized Solar Cell (DSSC) Using Rhodanine Acetic Acid as Electron Withdrawing Group - Sudarlin Sudarlin (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Modification of cyanidin as sensitiser on Dye Sensitized Solar Cell (DSSC) has been carried out theoretically in this study using rhodanine acetic acid. The rhodanine acetic acid as electron withdrawing group can increase the electron density of the LUMO state, so injection of the excited electron to the semiconductor can also be increase. The theoretical method used is DFT/B3LYP theory by NWChem software. The calculation shows that the LUMO energy of cyanidin rhodanine acetic is higher than cyanidin, so electron injection to the conduction band of the semiconductor is easier. This condition is supported by reduced of HOMO-LUMO energy gap, so the range of the sunlight that can be involved in the electron excitation process is wider. In addition, the LUMO electron density of the cyanidin rhodanine acetic is localized at rhodanine acetic which makes the distance of the excited electron is closer to the semiconductor, thereby facilitating electron injection.